Physicochemical Properties and Surfaces Morphologies Evaluation of MTA FillApex and AH Plus - Álvaro Henrique Borges; Maura Cristiane Gonçales Orçati Dorileo; Ricardo Dalla Villa; Alexandre Meireles Borba; Tereza Aparecida Delle Vedove Semenoff; Orlando Aguirre Guedes; Cyntia Rodrigues Araújo Estrela; Matheus Coelho Bandeca (The Scientific World Journal)
The solubility, pH, electrical conductivity, and radiopacity of AH Plus and MTA FillApex were evaluated. In addition, the surfaces morphologies of the sealers were analyzed by using scanning electron microscopy. For pH test, the samples were immersed in distilled water at different periods of time. The same solution was used for electrical conductivity measurement. The solubility and radiopacity were evaluated according to ANSI/ADA. Statistical analyses were carried out at 5% level of significance. MTA FillApex presented higher mean value for solubility and electrical conductivity. No significant difference was observed in the mean values for pH reading. AH Plus presented higher radiopacity mean values. MTA FillApex presented an external surface with porosities and a wide range of sizes. In conclusion, the materials fulfill the ANSI/ADA requirements when considering the radiopacity and solubility. AH Plus revealed a compact and homogeneous surface with more regular aspects and equal particle sizes.